Organizational Commitment Mediating the Influence of Training and Work Motivation on Employee Performance - Nawangsari, Evi; Mintarti, Mintarti; Sudjatno, Sudjatno (Interdisciplinary Social Studies, 2023)
ackground: Along with the development of technology and information and the need for education in Indonesia which continues to increase, it has resulted in competition among existing universities. Based on data from the Secretariat of the Directorate General of Higher Education, the number of universities in Indonesia reached 4,593, of which 74.09% of the number followed the education reference provided by the Directorate General of Higher Education, Research and Technology (DIKTI). This results in every existing college must be able to improve quality in order to compete with other universities. Aim: This study discusses the effect of training and work motivation on employee performance with organizational commitment as a mediation variable. Method: This research is explanatory research with a quantitative type of research.  The sampling technique used in this study was non-probability sampling using saturated samples. Statistical analysis in this study was processed using the SEM-PLS analyzer. Findings: Organizational commitment mediated the role of the influence of work motivation on the performance of educational personnel at the Faculty of Agriculture, University of Brawijaya. It is because when employees have very high motivation and the motivation has been fulfilled by the organization, they will be more loyal to the organization and will indirectly improve employee performance.